Pemanfaatan Media Pembelajaran Berbasis Teknologi Digital dalam Pembelajaran PAK untuk Meningkatkan Prestasi Belajar Peserta Didik di SMPK Swadaya Tuakepa - Margareta Bakang Hayon; Yosep Belen Keban; Hermania Bhoki (CV. ALIM'SPUBLISHING, 2026)
This study was motivated by the importance of using digital technology-based learning media in Catholic Religious Education learning to improve students’ learning achievement. The development of digital technology requires teachers to use interesting and interactive learning media that are suitable for students’ needs. This study aimed to determine the use of digital technology-based learning media in Catholic religious education learning and its impact on students’ learning achievement at SMPK Swadaya Tuakepa. This study used a qualitative method with a descriptive approach. The research subjects consisted of the principal, the Catholic religious education teacher, and five students. Data were collected through interviews, observations, and documentation. The data were analyzed through data reduction, data presentation, and conclusion drawing. The results showed that digital technology-based learning media such as PowerPoint, learning videos, Canva, Kahoot, and Quizizz had been utilized well in the learning process. The use of digital media helped teachers explain learning materials more clearly and attractively so that students became more active, focused, and motivated in learning. In addition, the use of digital media also improved students’ intellectual abilities, cognitive strategies, attitudes, and skills. Therefore, digital technology-based learning media can improve the quality of Catholic religious education learning and students’ learning achievement at SMPK Swadaya Tuakepa.